Hexagonal boron nitride hollow capsules with collapsed surfaces: Chemical vapor deposition with single-source precursor ammonium fluoroborate*Project supported by the National Natural Science Foundation of China (Grant Nos. 51332005, 51372066, 51172060, 51202055, and 21103056). (9th June 2016) - Li 李, Xiaopeng 肖鹏; Zhang 张, Jun 军; Yu 郁, Chao 超; Liu 刘, Xiaoxi 晓喜; Abbas, Saleem; Li 李, Jie 杰; Xue 薛, Yanming 彦明; Tang 唐, Chengchun 成春
Abstract: SBA-15 (mesoporous SiO2 ) is used to stabilize and transfer F − in the NH4 BF4 CVD reaction for the first time, and a large-scale crystalline h-BN phase can be prepared. We successfully fabricate hollow h-BN capsules with collapsed surfaces in our designed NH4 BF4 CVD system. Optimum temperature conditions are obtained, and a detailed formation mechanism is further proposed. The successful SBA-15-assisted NH4 BF4 CVD route is of importance and enriches the engineering technology in the h-BN single-source CVD reaction.